(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The word Adhimantha indicates excessive churning type of pain. Adhimantha is compared with glaucoma in modern science to some extent. Clinical features of this disease vary depending upon Doshas involvement 4 types of Adhimantha was mentioned by our Acharyas. Glaucoma affects 2-3% of people over the age of 40 years 50% may be undiagnosed. primary open angle glaucoma (POAG) is the most common form, the disease is insidious and usually asymptomatic until it has caused a significant loss of visual field hence it is called as “silent thief of sight”. Glaucoma is a neurodegenerative condition that affects mainly nervous coat of eye and is associated with increased intraocular pressure when left untreated patients may gradually experience visual field loss and even lose their sight completely. It is the second leading cause of blindness around worldwide. It cannot be treated completely but it can be managed with Ayurvedic therapeutics to some extent by giving Sodhana chikista like Virechana and Raktomokshana, Kriyakalpas like Akshitarpan, Seka, Anjana, Aschyotana, Pindi, Bidalaka, Chakshsuya drugs and Mutrala drugs (diuretics) etc.